Self-bound droplet formation in two coupled Bose-Einstein condensates - Chiquillo Márquez, Emerson Evaristo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The main subject of this work is research the stable formation of droplets in Bose-Bose gases considering some extra elements to those already known in the description of conventional droplets. To this end, the study is carried out mainly through an effective quantum field theory in the the path-integral formalism. To ensure that the physical results are finite, we also use some basic aspects of renormalization by counterterms including regularization methods. So, we set key findings regarding to droplets with nonuniversal corrections to the interactions, in three, two, and one dimension, both at zero and finite temperature. We include three-dimensional Rabi-coupled droplets with nonuniversal corrections to the interactions at zero temperature. Droplets in two coupled Bose-Einstein condensates with dipole-dipole interactions both at zero and finite temperature are also explored.

O tema principal deste trabalho é pesquisar a formação estável de gotas em gases bosônicos acoplados, considerando alguns elementos extras àqueles já conhecidos na descrição das gotas convencionais. Para atingir esse objetivo, o estudo é feito principalmente por meio de uma teoria quântica de campos efetiva no formalismo da integral de trajetória. Para garantir que os resultados físicos sejam finitos, também usamos alguns aspectos básicos da renormalização por contratermos, incluindo métodos de regularização. Assim, estabelecemos descobertas em relação às gotas com correções não universais para as interações, em três, duas e uma dimensão, tanto em temperatura zero quanto finita. Em tres dimensões incluímos gotas com o acoplamento de Rabi e correções não universais para as interações em temperatura zero. Gotas em dois condensados de Bose-Einstein acoplados com interações dipolo-dipolo tanto em temperatura zero quanto finita também são exploradas.
Formação de gotas autoligadas em dois condensados ​​de Bose-Einstein acoplados
Keywords: Bose-Bose gases; Gaussian fluctuations; Quantum droplets; Matéria condensada.; Condensação de Bose-Einstein; Teoria quântica de campos